Polymorphism of cytotoxic T-lymphocyte clones that recognize a defined nine-amino-acid immunodominant domain of lymphocytic choriomeningitis virus glycoprotein. - Joly, E (J Virol, 1989)
To assess the heterogeneity of cytotoxic T lymphocytes (CTLs) directed against viral epitopes, we studied six class I major histocompatibility complex-restricted (H-2Db) CTL clones that recognize the same 9-amino-acid immunodominant epitope, amino acids 278 to 286 from envelope glycoprotein 2 (GP2) of lymphocytic choriomeningitis virus (LCMV). Using Southern blot analysis of beta-chain rearrangements, we found that each clone has a unique restriction pattern, providing evidence of the independent derivation of the clones and suggesting that the clones express different beta-chain sequences for their T-cell receptor. All these clones killed syngeneic target cells infected with strain Armstrong or WE of LCMV; however, two of the six clones failed to recognize target cells infected with the Pasteur strain of LCMV. Sequence analysis of LCMV Armstrong, WE, and Pasteur GP in the region of amino acids 272 to 293 demonstrated a single-amino-acid substitution at amino acid 278 in the region of the defined epitope in the Pasteur strain. Interestingly, one of the two CTL clones that failed to lyse LCMV Pasteur-infected target cells nevertheless efficiently and specifically killed uninfected target cells coated with the appropriate LCMV Pasteur peptide, while the other clone failed to do so. This indicated a dichotomy between processing of the synthesized protein initiated by infection and a peptide exogenously applied. Dose-response studies utilizing several peptides with substitutions in GP amino acid 278 indicate that CTL recognition occurs at the level of a single amino acid and suggest that this difference is likely recognized at the level of the T-cell receptor. IMAGES: